Optimal Resource Allocation in Aerial Reconfigurable Intelligent Surface-Aided Communications for Beyond 5G - Nguyen, Minh-Hien T.; Garcia-Palacios, Emiliano (2021 IEEE International Symposium on Dynamic Spectrum Access Networks (DySPAN), 2021)
To exploit the benefits of unmanned aerial vehicle (UAV) and reconfigurable intelligent surface (RIS) technologies, in this work, we propose the use of multiple passive RISs, each of which is attached to a UAV, in order to extend network coverage from a massive multiple-input multiple-output base station. Our aim is to maximise the total network throughput by finding the optimal power control coefficients at the base station and the phase shifts of the multiple RISs used in the system, which will be jointly solved subject to the power consumption constraints, UAV-RIS deployment, and quality-of-service required at the users. Numerical results demonstrate that our proposed method outperforms benchmark schemes in terms of total network throughput.